RNA-Seq data from Ovarian Tumours - Moskov, Mikaela; Hedlund, Julia Lindberg; Gyllensten, Ulf; Sundfeldt, Karin; Stålberg, Karin; Enroth, Stefan (Uppsala University, 2025)
The data presented in this item contain sensitive information that cannot be shared openly. Work on depositing the data in FEGA Sweden has been initiated. FEGA Sweden is a national node of the Federated European Genome-phenome Archive (FEGA), which allows data to be shared under controlled access. The datasets in FEGA Sweden are findable through the European Genome-phenome Archive web portal (https://ega-archive.org).

This dataset refers to the raw data used in the preprint "Deep plasma proteomics identifies and validates an eight-protein biomarker panel that separate benign from malignant tumors in ovarian cancer" available on MedRxiv (DOI: 10.1101/2024.10.10.24315232v1)

Data Set Description

Samples: 81 fresh frozen tumor tissue samples, either benign or malignant, from women with suspected ovarian cancer were used for analysis of mRNA expression.

Library Preparation and Sequencing: Sequencing libraries were prepared from 122-194 ng (three samples), 200 ng (seven samples) or 500 ng (71 samples) total RNA using the TruSeq stranded mRNA library preparation kit (cat# 20020595, Illumina Inc.) including polyA-selection. The libraries were then sequenced on a NovaSeq 6000 system (Illumina Inc.) on S4 flowcells with version 1.5 sequencing chemistry on three lanes. Paired-end sequencing of with read lengths of 150 bp was used.

Library preparation and sequencing was performed by the SNP&SEQ Technology platform, SciLifeLab, National Genomics Infrastructure Uppsala, Sweden.
Keywords: Cancer genetics; Genomics and transcriptomics; Medical and Health Sciences; Medicin och hälsovetenskap; Genetics and Genomics; Genetik och genomik; Cancer and Oncology; Cancer och onkologi